(untitled) (Indonesian Journal of Agrarian Law, 2026)
Abstract Rapid Urbanization in shout East Asia, particularly in Indonesia and Thailand, has caused savere spatial fragmantation and a proliferation of urban slums, necessitating sustainable land reorganization Without forced evictions. The paper aims to anelyze the emperical dynamics of land development,compare foundational financing structures, and identify long-term succes factors for spatial adjustments.Ultilizing a qualitative comparative methodology through socio-legal and economic-managerial lenses, the study examines land consolidation in Indonesia an Land Redjustments in Thailand. Results show that while Indonesia’s framework addreses multi-dimensional social issues and disaster recovery,its implementation is hindered by bureaucratic silos,sectoral egos, and complete dependency on public budgets due to a lack of marketable reserve land. Conversely,Thailand’s approach achieves financial self-sufficiency and regulatory clarity through its 2004 Act, commercializing reserve land and leveraging grassroots community savings.The main contribution of this research lies in its synthesis of diverse land typologies from urban slums to post-disaster zones and its strategic structural comparison , filling an analytical gap in single-location and purely normativist literature. The study concludes that long-term structural success relies on financial autonomy and unfied institutional mechanisms rather than tokenistic participatory rhetoric. It is recommended that Indonesia implements a radical policy reorientation by establishing local intergrated Land Consolidation Desks to eliminate institutional fragmentation, adopting Land Value Capture modes alongside Bank Tanah mechanisms to lock land value, and shifting community engagement from mere administrative consent to substantive financial shareholding to avoid gentrification. Keywords: Land Consolidation, Land Redjustmen, Urban Slums, Financing Schemes, Comparative Spatial Management, Agrarian Jutice.